Características nutricionais de grãos secos destilados com solúveis produzidos em Mato Grosso e seus efeitos sobre o desempenho e viabilidade econômica em suínos - Santos, Tatiane Izabel Silva dos (2017)
The production of biofuels from energy foods results in co-products that can be used to feed pigs, such as dried distillers grains with solubles (DDGS). The use of DDGS co-product obtained from the production of corn ethanol in pig feed aims to reduce production costs while maintaining the economic viability, nutritional quality and performance of the animals. However, nutritional variation and physico-chemical characteristics among DDGS sources may be a limiting factor in their use. The objective of this work was to estimate the nutritional value of corn DDGS sources in the State of Mato Grosso, its effects on the performance of pigs fed different levels of DDGS and economic viability. Three studies were carried out. Study 1: Four sources of DDGS were evaluated for dry matter (DM), mineral matter (MM), crude protein (CP), ethereal extract (EE), neutral detergent fiber (NDF) and crude energy (GE). The nutritional value of energy sources was estimated by means of energy prediction equations. The values of estimated gross energy (GEe), estimated digestible energy (DEe), estimated metabolizable energy (MEe) and estimated net energy (NEe) were significant among the sources evaluated. Study 2: 40 castrated male mestizos of commercial lineage, with initial weight of 72.69 ± 5.66 kg, distributed in a randomized complete block design with 4 treatments and 5 replicates were used. The treatments were composed of diets based on corn and soybean meal with addition of DDGS at levels of 100, 200 and 300 g kg-1 , formulated to meet the requirements of the category. The performance of the animals was evaluated by daily dietary intake (ADFi), Daily Diary gain (ADG), feed conversion (G:F) and mean weights of each experimental unit. Pigs fed levels up to 300 g kg-1 DDGS did not present the affected performance variables, however, the increase in DDGS levels linearly reduces the weight of pigs in the total period. Study 3: Based on the results of study 2, the economic viability analysis of the use of DDGS was performed using cost per weight gain (CWG), economic efficiency index (EEI) and cost index (CI). Addition of levels of up to 300 g kg-1 of DDGS did not affect the cost of weight gain of pork produced, the Economic Efficiency Index and Cost Index. The use of DDGS in the diet of pigs has shown good results on the performance of the animals, however, a cautious evaluation regarding the viability of the use is necessary, depending on the inclusion.